KOMUNIKASI DOSEN DENGAN MAHASISWA DALAM KEGIATAN PEMBELAJARAN MELALUI METODE CERAMAH - AMINUDIN JUNAEDI; TABRANI SJAFRIZAL (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine the communication of lecturers and students in learning activities through varied lectures. This study uses a qualitative research method, with a lecturer analysis unit of the Faculty of Communication Sciences. The results showed that learning communication was established when lecturers transfer knowledge to students in the classroom learning through lectures, ideally lectures run normally in class, lecturers deliver lecture material through lectures running smoothly and safely, orderly all students seriously listening to learning material until completion of lectures. , but in reality, in the first hour only the situation in the lecture was supportive, but in the next hour the lecture atmosphere was often not conducive. One student's lack of focus is caused by lecturers' lectures that are monotonous and less varied, this is the reason for the shift of student attention. By knowing the weaknesses of this lecture method, then the lecturer can explore the unique and specific things he has, to present lectures that are more varied both in terms of style, appearance, voice intonation, learning media to be explored deeper, so as to produce varied lectures that attract students, and ultimately results in optimal learning quality.